Differential expression of non-coding RNAs and continuous evolution of the X chromosome in testicular transcriptome of two mouse species - Homolka, David; Ivanek, Robert; Forejt, Jiri; Jansa, Petr (PloS one, 2011)
BACKGROUND: Tight regulation of testicular gene expression is a prerequisite for male reproductive success, while differentiation of gene activity in spermatogenesis is important during speciation. Thus, comparison of testicular transcriptomes between closely related species can reveal unique regulatory patterns and shed light on evolutionary constraints separating the species. METHODOLOGY/PRINCIPAL FINDINGS: Here, we compared testicular transcriptomes of two closely related mouse species, Mus musculus and Mus spretus, which diverged more than one million years ago. We analyzed testicular expression using tiling arrays overlapping Chromosomes 2, X, Y and mitochondrial genome. An excess of differentially regulated non-coding RNAs was found on Chromosome 2 including the intronic antisense RNAs, intergenic RNAs and premature forms of Piwi-interacting RNAs (piRNAs). Moreover, striking difference was found in the expression of X-linked G6pdx gene, the parental gene of the autosomal retrogene G6pd2. CONCLUSIONS/SIGNIFICANCE: The prevalence of non-coding RNAs among differentially expressed transcripts indicates their role in species-specific regulation of spermatogenesis. The postmeiotic expression of G6pdx in Mus spretus points towards the continuous evolution of X-chromosome silencing and provides an example of expression change accompanying the out-of-the X-chromosomal retroposition.
Keywords: molekulární evoluce; retroelementy; druhová specificita; testis; Evolution, Molecular; X Chromosome; Meiosis; zvířata; nekódující RNA; myši; Retroelements; Glucosephosphate Dehydrogenase; Mice; RNA, Untranslated; RNA, Small Interfering; Gene Silencing; chromozom X; meióza; antisense RNA; malá interferující RNA; umlčování genů; glukosa-6-fosfátdehydrogenasa; Male; Testis; RNA, Antisense; transkriptom; Species Specificity; Transcriptome; Animals; mužské pohlaví